MENTOR AND STUDENT (B.PASTERNAK AND A.VOZNESENSKY) - Abdaliyeva, Gulistan Rafikovna; Otakhonova, Maxinur Botirovna (SCIENCE and SOCIETY, 2026)
This article examines the relationship between poets Boris Pasternak and Andrei Voznesensky. Boris Pasternak was Voznesensky’s mentor and blessed his first steps into poetry. A.Voznesensky carried love and admiration for his mentor through his whole life.